Human Resources Development Through The Human Capital Model - Rosyadi Rosyadi (Cita konsultindo, 2023)
Regional government and community leadership requires the development of quality human resources as implementers of development so that they are capable and resilient in realizing the national goals of promoting general welfare, educating the nation's life in a free, independent, united, sovereign, just and prosperous national life. One way to develop human resources is the human capital method. Human capital is an investment made with the aim of increasing a higher level of consumption in the future, which is obtained through education. In addition, this investment also aims to increase human productivity. The form of this research is descriptive research, the purpose of this research is to describe in general the conditions of human resource development in West Kalimantan and efforts to increase human resources with a human capital approach. The results of this study suggest that efforts must be made by the government and society together, namely through an ethical and moral approach that involves the role of religion in society, human capital to improve the quality of life of human resources and also we must be able to contextualize human resource development through a local cultural approach or local culture in the region of West Kalimantan.